REMEDIASI ELEKTROKINETIK TERHADAP LOGAM-LOGAM BERAT MENGGUNAKAN ELEKTRODA 2-D HEXAGONAL PADA TANAH DARI TEMPAT PEMBUANGAN AKHIR (TPA) TOISAPU AMBON - Noke Kesaulya; Yuli T Filindity (Molluca Journal of Chemistry Education (MJoCE), 2019)
The Electrokinetic Remediation process for soil using 2-D hexagonal electrode has been done with observing pH and concentration of heavy metals, such as Hg, Zn and Pb of soil before, during and after processing the electrokinetic. Results of research indicated that contents of soil in Hg metal ions were 1.088 ppm; Zn =0.135 ppm and Pb, 0.115 ppm. Concentration of the metal ions was different to each time because rubbish in TPA was also different. Process efficiencies for Hg were 24.78 %; Zn, 33.71 % and Pb, 10.13 %. Efficiency process of electrokinetic remediation was highly influence by distance of cathode and duration of remediation process. Closer distance from cathode, time taken for remediation process was shorter, also the opposite